The South Baghdad Electrical Station and its Environmental Impact on the Tigris River - Nora R. Majeed; Jinan Abdul Ameer Abass (College of Education for Women, 2019)
The South Baghdad electrical station located on the eastern bank of the Tigris River south of Baghdad city was selected within the municipality of Karrada between  two  latitude ( 330 15 , 33 0  18 )North  and  longitude ( 44 0  27 , 44 030 ) East . The purpose of the study is to determine the contribution of the station to the effect of pollution of the Tigris water by taking water samples at the station site and two sites, one before and the other after the station, distributed over time periods of three months between each sample of water and the beginning of August and November Shabat and Mayar and analyzed water samples physically, chemically and biologically, It was found that the highest percentage of pollution was at the site of the station and the highest percentage of pollution was in August and reached (52.94) % as the contaminants that crossed the border were allthat  turbidity and electrical  conductivity  and  temperature  and Chemical Oxygen  Demandand Total Suspended Solids and Phenols and Biological Oxygen Deman and Total Plate Count and Fecal Coliform Bacteria, And then it was in November (47.05) % and represented by eachturbidity, electrical  conductivity  and Chemical Oxygen  Demandand Total Suspended Solids and Phenols and Biological Oxygen Deman and Total Plate Count and Fecal Coliform Bacteria , The same percentage was in May (47.05) % turbidity and  temperature  and Chemical Oxygen  Demandand Total Suspended